(3JWhQ GdacQ GdGbJUGOj (B:s (3ef GdeQcfJjdjI Gdi GdcdGSjcjI (B/s - (3edGc, hSGes ((3HjQhJ(B: s (3OGQ Gdefgd GddHfGfj(B, s, 2011)
1) (3GdeQcfJjdjI aj ChQhHG (B: (3GdeQcfJjdjI GdaQfSjI , GdeQcfJjdjI aj HQjWGfjG h GdeQJcRGJ GdfXQjI ddeQcfJjdjI h GdKZQGJ GdCge GdJj GYJQJgG (B2) (3GdajRjhbQGWjI CMO aQhY GdeOQSI GdcdGSjcjI GdaQfSjI (B: (3CYdGe GdajRjhbQGWjI GdChSY TgQI , GdJMdjd GdChSY ddajRjhbQGWjI (B3) (3GdeOQSI GdcdGSjcjI (B: (3BOe SejK hGVY GdQcGFR GdCSGS ddfXQjI GdcdGSjcjI , fXQjI GdScGf h GdeQOhOGJ GdeJfGbUI h GdQjY h GdJaGVdj h GdCReGJ YfO (Bmalthus (3GdESgGe GdcdGSjcj ef NdGd eG jYQa HfXGe (BRICARDO (3bGfhf (BSAY (3h GdfXQjI GdcdGSjcjI Mhd GdfbO (B.s
Keywords: (3GdGbJUGOs; (3GdEbJUGO GdcdGSjcjs; (3GdacQ GdEbJUGOjs